The senatorial courtesy game: explaining the norm of information vetoes in advice and consent nominations - Jacobi, Tonja (2006)
Despite the contentiousness of advice and consent nominations, the Senate usually rejects a candidate to whom a home senator objects. Using game theory, this article explains the persistence of senatorial courtesy and maps its effects on which candidates succeed. The greater salience of a home nomination allows retaliation and reciprocity in a repeated game to elicit support for a veto, even under adverse conditions. Comparative statics indicate the range of the president's feasible nominees and show which players gain and lose from the practice. Most notably, the president can benefit from an exercise of senatorial courtesy. - Reproduced.
Keywords: United States. Congress - Senate; Parliament